Blockchain-Based Value-Added Tax System: A Systematic Review - Vahideh Ghanooni Shishavan; Shaban Elahi; Sadegh Dorri Nogoorani; Ali Yazdian Varjani (تحقیقات مالی)
ObjectiveBlockchain finds application in the public sector, notably in the tax system. The extant literature points to the benefits of employing blockchain in the tax system. A review of studies provides a general view of why and how to implement blockchain technology as well as the identification of existing defects to solve it. In this paper, we investigate how to implement blockchain technology in the value-added tax (VAT) system and answer three questions through a systematic literature review: (1) what are the characteristics of blockchain that can help in the VAT system; (2) what is the appropriate blockchain framework for the VAT system; and (3) what are the appropriate solutions to protect privacy in a blockchain-based VAT system. MethodsWe conducted a systematic literature review following the guidelines proposed by Okoli and Prisma flow diagrams. The screening process was carried out in three stages to ensure that each article fits the research questions. The first article in this field was published in 2017, and the number of articles has risen significantly since then.ResultsThe increasing number of papers reflects the growing interest in implementing blockchain technology. Statistical charts indicate that approximately 60% of the documents are conference papers. Our systematic literature review revealed that blockchain technology can play a crucial role in enhancing the VAT system, particularly in the electronic invoicing process. By identifying existing challenges in electronic invoices, such as transaction forgery, the long process of issuing electronic invoices, and hacking of the central database, blockchain technology, with its features like decentralization, tamper-proofness, transparency, and automation, emerges as a suitable solution. We propose a blockchain-based architecture and a five-step process that includes: authentication and authorization, sending electronic invoice(s), storing the e-invoice(s) in the blockchain, reviewing and verifying the e-invoice(s), and last but not least, payment of VAT. For the security and privacy of taxpayers, we propose the use of a private blockchain, opting for a permissioned blockchain to ensure that only trusted users are part of the network. Network users can include companies, banks, tax authorities, and auditors. In the third and fifth steps, the utilization of smart contracts is recommended. Smart contracts play a role in documenting taxes in the third step. Furthermore, in this stage, leveraging off-chain storage is possible, where the data hash is stored in the blockchain, and the original data is kept separately. In the fifth step, a smart contract can periodically calculate VAT to be deducted from the payers' accounts by banks. Encryption alone cannot guarantee the privacy of electronic invoices, and while zero-knowledge proofs seem to be a suitable solution, they come with considerable complexities. ConclusionAccording to the inherent characteristics of the blockchain, it can be concluded that a blockchain is a suitable option for the VAT system and the right architecture is a permissioned private blockchain. However, further study is required to address privacy concerns.